Municipal Tourism Planning in an Island Territory: The Case of Ribeira Grande in the Azores. Issue 3 (4th May 2021) - Ponte, João Crispim; Couto, Gualter; Pimentel, Pedro; Sousa, Áurea; Oliveira, André
ABSTRACT: This paper discloses the strategic tourism planning process carried out in the Municipality of Ribeira Grande. This is an important municipality of the Azores, although with a poor tourism performance. Recognizing this gap, Ribeira Grande was the first municipality in the Region to develop a strategic tourism development plan. The process included statistical analysis, based on different statistical methods, on tourists' responses to a questionnaire. The strategic plan had to be focused on the most differentiating local resources and attractions and had to fit into the regional development strategy for the Azores. Local stakeholders and tourists were consulted and they selected nature-based tourism and local natural resources as the destination's most important features. However, tourists pointed out the need for more adventure tourism packages and more walking trails. All the inputs resulted in the definition of four strategic products: nautical tourism, cultural tourism, wellness tourism, and nature tourism.